Analysis of drought stress tolerance in doubled haploid lines of green super rice at the vegetative stage - Siti Nurhidayah; Bambang Sapta Purwoko; Iswari Saraswati Dewi; Willy Bayuardi Suwarno; Iskandar Lubis; Wira Hadianto; Arief Munandar (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Current climate change has caused drought in various regions, which has decreased rice yields. Green super rice (GSR) has the characteristic of being tolerant to water limitation. GSR lines were bred through anther culture technique to obtain doubled haploid (DH) plants. This study aimed to analyze the response of DH GSR lines to drought stress at the vegetative stage and identify potential lines based on the weighted selection index. The experiment was arranged in a randomized complete block design with three replications. The materials used consisted of twenty DH lines, Inpari 42 Agritan GSR, and Inpari 18 as check varieties, Salumpikit as a drought-tolerant check, and IR 20 as a drought-sensitive check. Qualitative data were analyzed using the non-parametric Friedman test. The result showed different responses among the lines for leaf rolling, leaf drying, and recovery ability. Line SN14 exhibited moderate leaf drying and showed improvement to mild tolerance during the recovery phase. Nine lines (SN12, 14, 32, 40, 51, 57, 58, 59, and 60) were selected using a selection index based on leaf rolling, leaf drying, and recovery ability. These lines can be further tested for drought tolerance tests until the reproductive stage, and the tolerant lines could be useful for future development. Keywords: abiotic stress; anther culture; climate change; selection index; water limitation